Co-effect of minerals and Cd(II) promoted the formation of bacterial biofilm and consequently enhanced the sorption of Cd(II). (March 2020) - Xu, Shaozu; Xing, Yonghui; Liu, Song; Luo, Xuesong; Chen, Wenli; Huang, Qiaoyun
Abstract: Heavy metal pollution is very common in soils. Soils are complex systems including minerals, bacteria, and various other substances. In Cd(II) contaminated soil, the combined effects of clay minerals and heavy metals on bacterial biofilm and Cd(II) adsorption are unappreciated. Our study showed that the combination of clay minerals (goethite, kaolinite, and montmorillonite) and heavy metals promoted Serratia marcescens S14 biofilm development significantly more than clay minerals or Cd(II) alone. The amount of biofilm after binary treatment with clay minerals and Cd(II) was 2.3–7.3 times than that in control. Mineral-induced cell death and the expression of the fimA, bsmA, and eps were key players in biofilm formation. Binary treatment with montmorillonite and Cd(II) significantly enhanced biofilm development and consequently increased the adsorption of Cd(II). Cd(II) removal is the result of co-adsorption of bacteria and minerals. Bacterial biofilm played an important role in Cd(II) adsorption. FTIR spectroscopy showed the components of biofilm were not affected by minerals and revealed the functional groups –OH, –NH, –CH2, –SH, –COO participated in Cd(II) immobilization. Our findings are of fundamental significance for understanding how minerals and Cd(II) affect biofilms and thereby enhance Cd(II) adsorption and predicting the mobility and fate of heavy metals in heavy metal-contaminated soil. Graphical abstract: Image 1 Highlights: Minerals and Cd(II) obviously promoted biofilm production and thereby enhanced Cd(II) adsorption. Cd(II) removal is the result of co-adsorption by bacteria and minerals. Bacterial biofilm played an important role in Cd(II) adsorption. Clay minerals affected the biofilm formation but did not affect its components. Abstract : Co-existence of montmorillonite and Cd(II) enhanced biofilm development and hence increased Cd(II) adsorption.